Resolving the Dilemma of Unemployment Rate Hysteresis Versus the Natural Rate Hypothesis in India - Singh, Deepti (Asian Journal of Applied Economics, 2025)
This study investigates the presence and degree of hysteresis in India’s unemployment rates, with particular attention to gender disparities across pre- and post-COVID-19 periods. Using quarterly data from Q2 2018 to Q2 2025, the analysis employs standard unit root tests, unit root tests with structural breaks, and Variance Ratio (VR) analysis to evaluate whether unemployment follows a persistent random walk—indicative of strong hysteresis—or exhibits mean-reverting behavior consistent with the natural rate hypothesis. Results from conventional unit root tests support the natural rate hypothesis, while structural break tests suggest the presence of non-stationarity, indicating a mild form of hysteresis. The VR analysis reinforces this mixed conclusion, revealing moderate mean reversion alongside limited shock persistence. Overall, the findings suggest that the natural rate hypothesis holds predominantly in India, although asymmetric labor market adjustments—especially during major disruptions such as the COVID-19 pandemic—indicate that mild hysteresis effects persist. These results imply that structural labor market reforms and targeted upskilling policies are more effective than prolonged cyclical interventions in ensuring long-run employment stability.